Electrocardiographic abnormalities in young healthy sheep and goats - Sudhakara Reddy, B; Venkatasivakumar, R.; Sivajothi, S.; Pridhvidhar Reddy, Y. V. (International Journal of Biological Research, 2014)
Electrocardiographic studies were done in clinically apparently healthy young sheep (26) and goats (32) in Andhra Pradesh. The electrocardiograms were recorded in standard base apex lead system. Five types of cardiac arrhythmias have been detected in this study, namely sinus tachycardia (18.9%), respiratory sinus arrhythmia (8.6%), sinoatrial block (6.8%), second-degree atrioventricular block (3.4%) and ventricular premature complex (1.7%). These abnormalities were recorded in both sheep and goat. Keywords: ECG, Young Sheep, Young Goats, Cardiac Arrhythmia.